Finite element analysis for the evaluation of the structural behaviour, of a prosthesis for trans-tibial amputees - Omasta, Milan; Paloušek, David; Návrat, Tomáš; Rosický, Jiří (Medical engineering & physics, 2012)
The finite element analysis (FEA) has been identified as a useful tool for the stress and strain behaviour determination in lower limb prosthetics. The residual limb and prosthetic socket interface was the main subject of interest in previous studies. This paper focuses on the finite element analysis for the evaluation of structural behaviour of the Sure-flex™ prosthetic foot and other load-bearing components. A prosthetic socket was not included in the FEA. An approach for the finite element modelling including foot analysis, reverse engineering and material property testing was used. The foot analysis incorporated ground reaction forces measurement, motion analysis and strain gauge analysis. For the material model determination, non-destructive laboratory testing and its FE simulation was used. A new, realistic way of load application is presented along with a detailed investigation of stress distribution in the load-bearing components of the prosthesis. A novel approach for numerical and experimental agreement determination was introduced. This showed differences in the strain on the pylon between the experimental and the numerical model within 30% for the anteroposterior bending and up to 25% for the compression. The highest von Mises stresses were found on the foot-pylon connecting component at toe off. Peak stress of 216MPa occurred on the posterior adjusting screw and maximum stress of 156MPa was found at the neck of the male pyramid.
Keywords: zatížení muskuloskeletálního systému; Prosthesis Design; Finite Element Analysis; Tibia; tibie; mužské pohlaví; Adult; Amputees; Weight-Bearing; Stress, Mechanical; protézy - design; Humans; amputovaní; mechanický stres; analýza metodou konečných prvků; dospělí; Prostheses and Implants; lidé; Male; protézy a implantáty